THE EXPLORATION OF TEACHERS’ EFFICACY IN TEACHING: COMPARATIVE STUDY IN INDONESIA AND MALAYSIA - Muhammad Nur Wangid; Ali Mustadi; Siti Eshah binti Mokshien (LPMPP Universitas Negeri Yogyakarta, 2020)
Teacher’s self-efficacy can be varied according to experience gained, experience obtained from other people, social influences, and also physical and psychological welfare. In the context of teacher’s efficacy in Indonesia and Malaysia, those are certain become different because it undergoes differently. The aim of the research is to convey the difference between teachers in Malaysia and Indonesia from the perspective of a teacher's efficacy in teaching. This research is a comparative study. The research subjects were elementary school teachers who were continuing their studies in post graduate programs at Yogyakarta State University and Sultan Idris University of Education. They are given a scale of teacher efficacy in teaching consisting of three sub-scale that is teacher’s efficacy in involving students in learning, executing learning process, and class management. Research result shows that actually, in general, there are no significant differences in teacher efficacy in teaching between teachers in Malaysia and Indonesia. However, if differences are seen from each factor, it appears that there are differences in the efficacy of teachers in involving students in learning, while the efficacy in instructional learning strategies, and efficacy in classroom management, there are still no significant differences.